Metformin inhibits cervical cancer cell proliferation via decreased AMPK O-GlcNAcylation. Issue 4 (4th July 2019) - Kim, Min Young; Kim, Yoon Sook; Kim, Minjun; Choi, Mee Young; Roh, Gu Seob; Lee, Dong Hoon; Kim, Hyun Joon; Kang, Sang Soo; Cho, Gyeong Jae; Shin, Jeong Kyu; Choi, Wan Sung
ABSTRACT: Metformin is a widely used drug for the treatment of type 2 diabetes. Antidiabetic drugs are also known to influence cancer progression, as high glucose levels affect both cancer and diabetes. Metformin induces cell cycle arrest in cancer cells, but the underlying mechanism remains unclear in cervical cancer system. Here, we examined how metformin affects cell cycle arrest and apoptosis in cervical cancer cells. Western blot analysis showed that levels of O-linked N-acetylglucosamine (O-GlcNAc) and O-GlcNAc transferase (OGT) were increased in cervical cancer cells; these effects were reversed by metformin treatment. Immunoprecipitation analysis was used to examine the interplay between O-GlcNAcylation and phosphorylation in HeLa cells, revealing that metformin decreased O-GlcNAcylated AMP-activated protein kinase (AMPK) and increased levels of phospho-AMPK compared to untreated cells. These results were associated with decreased cell cycle arrest and apoptotic cell death in HeLa cells, as shown by flow cytometry. Moreover, 6-diazo-5-oxo-L-norleucine (a glutamine fructose-6-phosphate aminotransferase inhibitor) or thiamet G (an O-GlcNAcase inhibitor) decreased or increased levels of O-GlcNAcylated AMPK, and increased or decreased levels of phosphorylated AMPK, respectively, suggesting that O-GlcNAc modification affects AMPK activation. Of note, we found that metformin treatment of HeLa cells increased the levels of p21 and p27 (which are AMPK-dependent cell cycle inhibitors), leading to increased cell cycle arrest and apoptosis in HeLa cells compared to untreated cells. These findings suggest that metformin may serve as a useful antiproliferative drug in cervical cancer cells, with potential therapeutic benefit.